Estrogen receptors alpha and beta: Opposing roles in hypothalamic-pituitary-adrenal axis function and stress-related behaviors - Weiser, Michael James, author; Handa, Robert, advisor (Colorado State University. Libraries, 2008)
Estradiol has reported effects on mood ranging from anxiogenic to anxiolytic and depressant to anti-depressant. These opposing actions of estradiol may be explained by the existence of two distinct estrogen receptor (ER) systems, ER alpha (ERα) and ER beta (ERβ). Furthermore, there exists a sex difference in stress-related psychiatric disorders such as anxiety and depression, for which women are more susceptible than men. Common to the pathology of these disorders is a dysfunctional hypothalamic-pituitary-adrenal (HPA) axis where glucocorticoid negative feedback is impaired leading to chronically high levels of circulating glucocorticoids. The HPA axis is the main neuroendocrine axis that governs physiological responses to stressors. In rodents, basal and stress-induced activity of the HPA axis is higher in females than in males. This suggests that, if transferable to humans, the sex difference observed in HPA axis function in animal models may help explain the female predisposition for certain psychiatric disorders. The studies described in this dissertation were aimed at characterizing the distinct roles for ERα and ERβ in HPA axis activity and stress-related behaviors. The studies in Chapter 3 examine the effect of estradiol signaling through ERα or ERβ on glucocorticoid negative feedback of the HPA axis. Results indicate that estradiol impairs glucocorticoid-dependent negative feedback by activating ERÎ± specifically at the level of the paraventricular nucleus (PVN). The studies in Chapter 4 examine the effect of estradiol signaling through ERα or ERβ on anxiety-like and depressive-like behaviors. Results indicate that selective activation of ERα is anxiogenic and depressant, whereas selective activation of ERβ is anxiolytic and antidepressant. Finally, the studies in Chapter 5 examine the effect of estradiol signaling through ERβ on behavior and HPA axis activity induced by glucocorticoid receptor (GR) activation in the central nucleus of the amygdala (CeA). Results indicate that delivery of a GR agonist to the CeA is anxiogenic and augments the HPA axis response to a stressor, and peripheral administration of an ERβ agonist blocks this effect. Collectively, these studies point to an antagonistic relationship between estradiol signaling through ERα and ERβ with respect to HPA axis activity and stress-related behaviors.
Keywords: anxiety; behavior; estrogen; estrogen receptors; glucocorticoids; hypothalamic-pituitary-adrenal axis; hypothalamus; stress; neurosciences; physiology